2020
DOI: 10.1101/2020.08.21.261883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inheritance of Rootstock Effects in Avocado (Persea americanaMill.) cv. Hass

Abstract: Grafting is typically utilized to merge adapted seedling rootstocks with highly productive clonal scions. This process implies the interaction of multiple genomes to produce a unique tree phenotype. Yet, the interconnection of both genotypes obscures individual contributions to phenotypic variation (i.e. rootstock-mediated heritability), hampering tree breeding. Therefore, our goal was to quantify the inheritance of seedling rootstock effects on scion traits using avocado (Persea americana Mill.) cv. Hass as m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Phylogeographic inferences, e.g., [ 91 ] will also be improved by assuming independent gene mutation models [ 92 ], yet unlinked marker inferences are already available [ 93 , 94 , 95 ]. Finally, harnessing polygenic adaptive scores from gene-based and genome-wide prediction models [ 96 , 97 , 98 ] will help building a more cohesive picture of natural drought adaptation and vulnerability [ 99 ] in the face of climate change [ 100 ], with a focus on highly heterogeneous mountain geographies [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogeographic inferences, e.g., [ 91 ] will also be improved by assuming independent gene mutation models [ 92 ], yet unlinked marker inferences are already available [ 93 , 94 , 95 ]. Finally, harnessing polygenic adaptive scores from gene-based and genome-wide prediction models [ 96 , 97 , 98 ] will help building a more cohesive picture of natural drought adaptation and vulnerability [ 99 ] in the face of climate change [ 100 ], with a focus on highly heterogeneous mountain geographies [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study limitation was to discuss how fruit traits correlation may be due to a common genetic architecture or genetic hitchhiking (i.e., pleiotropy). It could be better described by linkage disequilibrium patterns or genetic covariance matrix (Arenas et al., 2021; Reyes‐Herrera et al., 2020). Our study deliberated genomic context‐dependent (i.e., epistatic) interactions and trade‐offs among the study fruit traits (Blair et al., 2016; Buitrago‐Bitar et al., 2021; Cortés & Blair, 2018; Cortés et al., 2013; Cortés et al., 2020; López‐Hernández & Cortés, 2019), but we were afraid not to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic materials chosen in the study were suitable for inducing precocity and resistance in susceptible cacao clones in commercial plantations, either as grafts or rootstocks. Previous research on cacao and other fruit trees has found heritability and the contribution of additive genetic effects (Reyes-Herrera et al 2020, Fernández-Paz et al 2021, Canas-Gutiérrez et al 2022. The selection allows new early tests for resistance to witches' broom and black pod rot, both in seedlings and nurseries, as a strategy to accelerate the reproductive age of plants.…”
Section: E Santos Et Almentioning
confidence: 98%